Analysis of Asset Growth, Capital Structure to Profitability in Plantation and Food Crop Industry Sub-Sector Companies Listed on IDX - Sari, Pipit Buana (Journal of Community Research and Service, 2024)
This research aims to test and analyze Asset Growth, Capital Structure and Profitability. The location of this research is the Plantation and Food Crop Industry Sub-Sector Company which is listed on the Indonesian Stock Exchange. The type of data used is secondary data in the form of financial reports. The data analysis technique used is panel data regression analysis. The sample in this research is all companies in the Plantation and Food Crops Industry Sub Sector registered on the IDX, totaling 23 companies with a total of 92 financial reports. The independent variables of this research are asset growth and debt to equity ratio (DER). The dependent variable is measured by return on equity (ROE). The research results show that partially asset growth and debt to equity ratio (DER) have a positive and significant effect on return on equity (ROE). Meanwhile, simultaneously the Asset Growth and debt to equity ratio (DER) variables have a positive and significant effect on return on equity (ROE). The magnitude of the influence exerted by all variables is 65.73%.